The role of corporate governance principles in the disclosure of financial statements A case study of the National Electricity and Gas Distribution Company - Oum El Bouaghi Directorate - Touaitia , Tahar; Belghoul , Hichem (Journal of Research in Finance and Accounting, 2020)
The issue of governance is one of the most important new topics due to the financial crises that affected many economic companies in the countries of the world, and this is the reason for the necessity to study the principles of governance and its impact on disclosure. The financial data, and we chose a random sample consisting of 40 workers from the Regional Directorate for Electricity and Gas Distribution (Oum El Bouaghi), and this study relied on the questionnaire tool as the first axis included the demographic variables of the study individuals, the second axis on the principles of corporate governance, and the third axis to achieve the disclosure of financial data We have relied in this study on the descriptive and analytical approach, and in order to test the study hypotheses, we will rely on statistical methods such as simple regression coefficients, the study of stability factors in the questionnaire tool, and some central measures. At the end of this study we will present some recommendations to urge the employees of the Regional Directorate for Electricity and Gas Distribution (Oum El Bouaghi) to focus on the dimensions that gave bad results.